2007
DOI: 10.1128/iai.00664-06
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autoimmune Type 1 Diabetes by Gastrointestinal Helminth Infection

Abstract: Gastrointestinal nematode infections are prevalent worldwide and are potent inducers of T helper 2 responses with the capacity to modulate the immune response to heterologous antigens. Parasitic helminth infection has even been shown to modulate the immune response associated with autoimmune diseases. Nonobese diabetic (NOD) mice provide a model for studying human autoimmune diabetes; as in humans, the development of diabetes in NOD mice has been linked to the loss of self-tolerance to beta cell autoantigens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
162
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(177 citation statements)
references
References 52 publications
9
162
0
2
Order By: Relevance
“…220 However, other potential long-lasting consequences of acute T. muris infection remain unexplored. In contrast, H. polygyrus appears to be protective in several inflammatory models, 221,222 and this has been attributed to its ability to dampen inflammation by promoting the generation and function of regulatory T cells via some of its secreted proteins. 223,224 Hence, the hygiene hypothesis might apply only to a narrow group of nematodes and it is important that we distinguish between general phenomena of parasite infection (such as the importance of IL-13) and more specific ones (such as the contribution of eosinophils) if we are to apply our knowledge to patients in the clinic.…”
Section: Resolutionmentioning
confidence: 99%
“…220 However, other potential long-lasting consequences of acute T. muris infection remain unexplored. In contrast, H. polygyrus appears to be protective in several inflammatory models, 221,222 and this has been attributed to its ability to dampen inflammation by promoting the generation and function of regulatory T cells via some of its secreted proteins. 223,224 Hence, the hygiene hypothesis might apply only to a narrow group of nematodes and it is important that we distinguish between general phenomena of parasite infection (such as the importance of IL-13) and more specific ones (such as the contribution of eosinophils) if we are to apply our knowledge to patients in the clinic.…”
Section: Resolutionmentioning
confidence: 99%
“…Indeed, animal models of arthritis, 22 type I diabetes, [12][13][14]21,24 Graves hyperthyroidism, 25 experimental autoimmune encephalitis 15,26 and colitis [16][17][18] have all been inhibited or ameliorated by infections with helminth parasites or parasite-derived products. In this study, we found that infection with filarial helminths also protects against autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…6 Experimentally, a number of helminth parasites, including the trematode Schistosoma mansoni and the nematodes Heligmosomoides polygyrus and Trichinella spiralis, prevent the onset or suppress the severity of type 1 diabetes in non-obese diabetic (NOD) mice, [12][13][14] experimental autoimmune encephalitis 15 and experimental colitis. [16][17][18] A clinical trial demonstrated that oral administration of porcine whipworm eggs improves symptoms in patients with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively slow response of NOD mice to primary infection with H. bakeri (Saunders et al 2007) and to repeated infections, this experiment has clearly shown that when the time frame under the latter protocol was extended beyond that normally used under repeated infection regimens (6 weeks), rejection of worms did occur. However, it was further slowed when NOD alleles of genes mapping in the region between D1Mit478 (Chr1:51 981 710) and D1mit134 (Chr1:80 264 451) on MMU1 were replaced by those from the very poor responder strain C57Bl/10.…”
Section: Discussionmentioning
confidence: 81%